2012
DOI: 10.1002/jpln.201100143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar compared to organic and inorganic fertilizers on soil quality and plant growth in a greenhouse experiment

Abstract: Our contemporary society is struggling with soil degradation due to overuse and climate change. Pre‐Columbian people left behind sustainably fertile soils rich in organic matter and nutrients well known as terra preta (de Indio) by adding charred residues (biochar) together with organic and inorganic wastes such as excrements and household garbage being a model for sustainable agriculture today. This is the reason why new studies on biochar effects on ecosystem services rapidly emerge. Beneficial effects of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
234
5
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(281 citation statements)
references
References 44 publications
35
234
5
7
Order By: Relevance
“…The non-significant effect of the treatments on yields observed in this study however contrasts the findings of (Yamato, Okimori, Wibowo, Anshori, & Ogawa, 2006;Schulz & Glaser, 2012) which found significant increase in crop yield as a result of biochar and fertilizer addition. They attributed it to biochar's ability to efficiently utilize nutrients by holding ammonium ions in soils and inhibiting nitrogen fertilizer nitrification.…”
Section: Yields Component Of Yamcontrasting
confidence: 99%
“…The non-significant effect of the treatments on yields observed in this study however contrasts the findings of (Yamato, Okimori, Wibowo, Anshori, & Ogawa, 2006;Schulz & Glaser, 2012) which found significant increase in crop yield as a result of biochar and fertilizer addition. They attributed it to biochar's ability to efficiently utilize nutrients by holding ammonium ions in soils and inhibiting nitrogen fertilizer nitrification.…”
Section: Yields Component Of Yamcontrasting
confidence: 99%
“…Carter et al (2013) confirmed that the biochar treatments were increased the final biomass, root biomass, plant height and leaf number of lettuce and cabbage in all the cropping cycles. Also, biochar addition to mineral fertilizers significantly increased plant growth (Schulz andGlaser, 2012, Biederman andHarpole, 2013).…”
Section: Plant Growth Morphological Traitsmentioning
confidence: 98%
“…Graber et al (2010) mentioned that treating tomato plants by biochar positively enhanced plant height and leaf size. Also, biochar addition to mineral fertilizers significantly increased plant growth (Schulz andGlaser, 2012, Biederman andHarpole, 2013). The biochar treatments were found to increase the final vegetative biomass, root biomass, plant height and leaf number of lettuce and cabbage in all the cropping cycles compared to no biochar treatments (Carter et al, 2013).…”
mentioning
confidence: 89%
“…For example, Jones et al [26] found no effects of biochar (50 t ha , respectively. In sandy soils this biochar input may be significant in terms of CEC, but may also be insignificant [27], while for many soils that already contain higher levels of organic matter and clay the impact of biochar may be inconsequential. Further studies need to report on the change in freshly incorporated biochar CEC values over time for biochars that have been placed in situ.…”
Section: Ammonium Adsorption and Leachingmentioning
confidence: 99%